2011
DOI: 10.1017/s002202991100015x
|View full text |Cite
|
Sign up to set email alerts
|

A psychrotrophicBurkholderia cepaciastrain isolated from refrigerated raw milk showing proteolytic activity and adhesion to stainless steel

Abstract: The proteolytic activity of a psychrotrophic strain of Burkholderia cepacia isolated from refrigerated raw milk was characterized. Bur. cepacia produced proteolytic activity during growth at refrigeration temperature, with maximum activity at pH 6-7. The enzyme showed relative thermal stability in the range 40-50°C during 25 min, and maintained 80% its initial activity at 76°C/30 s. Milk coagulation assay showed that the crude protease from Bur. cepacia caused coagulation from day 2 for skimmed milk, whereas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Bacteria found in raw milk are able to form biofilms and produce enzymes at various temperatures (Nörnberg et al . ; Cleto et al . ; Teh et al .…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria found in raw milk are able to form biofilms and produce enzymes at various temperatures (Nörnberg et al . ; Cleto et al . ; Teh et al .…”
Section: Introductionmentioning
confidence: 99%
“…The dominant genera observed during the days of the three treatments belonged to two classes, Gammaproteobacteria and Bacilli, with the class Gammaproteobacteria being dominant in almost every day, with an approximate average of 85% of the relative abundance (Figure 5A). The contaminating microbiota of refrigerated raw milk includes both Gram-positive and Gram-negative microorganisms, but the latter represents more than 75%, among which a large part belong to the Gammaproteobacteria class (Nörnberg et al 2011;Pinto et al 2015). observed that in the biofilms formed by the microbiota of raw milk at 7 ºC, Gammaproteobacteria and Bacilli represented about 50% each of the microorganisms identified.…”
Section: Microbial Diversity Of Biofilmmentioning
confidence: 94%